An analysis of Cape Town Municipality's approach to urban regeneration in the central business district and other business nodes - Liebenberg, Christiaan Rudolf (Stellenbosch : Stellenbosch University, 2012)
Thesis (MS en S)--Stellenbosch University, 2002.